Effect of essential oil of black cumin (Nigella sativa) on hematological profiles and total cholesterol levels of Wistar rats exposed by cigarette smoke - Rakhmawatie, Maya Dian; Muhammad Adzanta Al Afghani; Nurkomariah Zulhijjah; Andra Novitasari; Arief Tajally Adhiatma (Indonesian Journal of Pharmacology and Therapy, 2020)
Cigarette smoke contains toxic substances such as carbon monoxide, lead, cadmium, tar and hydrogen cyanide which can triggeroxidative stress and causeerythrocyte membrane damage and hemoglobin oxidation. In addition, it also contains nicotine which can increase the total cholesterol levels. Black cumin containing thymoquinone has been known for its antioxidant and anticholesterol activities. This study aimed to investigate the effect of black cumin extract on hematological profiles and total cholesterol levels of Wistar rats exposed by cigarette smoke. It was an experimental study with randomized posttest only control group design. Twenty Wistar rats (Rattus norvegicus) that divided into four groups were used in this study.The normal control group (N) was provided with standard feed,the negative control group (C) was exposed to the cigarette smoke with two pieces of cigarettes/day for 14 days, the treated groups were given black cumin extract 200mg/kg (T1) and 400mg/kg (T2) and exposed by cigarette smoke two pieces of cigarettes/day for 14 days. On day 15, blood samples from the rats were taken through the sinus orbitalis and then the erythrocyte, the hemoglobin and the total cholesterol levels were examined. Data were analyzed using the one-way ANOVA test and continued by the post-hoc test. The results showed the number of erythrocytes and hemoglobin levels of the T2 group was significantly higher than those of the C group (p<0.05). Although, total cholesterol levels of the T2 group was lower than that of other groups, however it was not significantly different (p>0.05). In conclusion, the administration of black cumin extract at 400mg/kg significantly increases the erythrocytes numbers and the hemoglobin levels in Wistar rats exposed by cigarette smoke.